Performance and Performativity in Contemporary Indian Fiction in English - Ioana Luca (Universitat Autònoma de Barcelona, 2018)
A review of Maria-Sabina Draga Alexandru's recent study of the work of Salman Rushdie, Arundhati Roy and Vikram Chandra